The impacts of climate change on animal health and economy: a way forward for policy option - Al-Amin, Abul Quasem; Alam, Gazi Mahabubul (Academic Journals Inc., 2011)
The national policy of developing countries is fundamentally suffered for climate change related research of animal health impacts, lack of policy alteration in emergency situations and lack of scenario research for impacts on ecosystem, distant animal health forecast, disease spread and migration. This study brings together the climate change issue and impacts on animal health and economy and its effecting factors to propose more effective strategies to control this social issue. Here, we emphasize prioritizing policy approaches of knowing how prefrences and climate may change in the distant future and selection of policy alternatives over which impacts are most relevant. The sound effective policy can be developed in the developing economy when there is an inter-linkage within each principal component such as on (a)national priorities,(b)specific research on climate animal health impacts, (c)scenario research of climate change in distant future, (d)alternative policy alteration in natural disaster and emergency and (e)gliobal outbreak of animal health impacts. This study attempts to investigate the inter-linkage of these indication and the possible planning lacking and concern focusing on climate change related animal health factors. The experiences from this studdy can be used for climate change related animal health impacts and potential economy policy in developing countries.